Digital soil: Robotically 3D-printed granular bio-composites. (June 2020) - Mitterberger, Daniela; Derme, Tiziano
Organic granular materials offer a valid alternative for non-biodegradable composites widely adopted in building construction and digital fabrication. Despite the need to find alternatives to fuel-based solutions, current material research in architecture mostly supports strategies that favour predictable, durable and homogeneous solutions. Materials such as soil, due to their physical properties and volatile nature, present new challenges and potentials to change the way we manufacture, built and integrate material systems and environmental factors into the design process. This article proposes a novel fabrication framework that combines high-resolution three-dimensional-printed biodegradable materials with a novel robotic-additive manufacturing process for soil structures. Furthermore, the research reflects on concepts such as affordance and tolerance within the field of digital fabrication, especially in regards to bio-materials and robotic fabrication. Soil as a building material has a long tradition. New developments in earth construction show how earthen buildings can create novel, adaptive and sustainable structures. Nevertheless, existing large-scale earthen construction methods can only produce highly simplified shapes with rough geometrical articulations. This research proposes to use a robotic binder-jetting process that creates novel organic bio-composites to overcome such limitations of common earth constructions. In addition, this article shows how biological polymers, such as polysaccharides-based hydrogels, can be used as sustainable, biodegradable binding agents for soil aggregates. This article is divided into four main sections: architecture and affordance; tolerance versus precision; water-based binders; and robotic fabrication parameters. Digital Soil envisions a shift in the design practice and digital fabrication that builds on methods for tolerance handling. In this context, material and geometrical properties such as material porosity, hydraulic conductivity and natural evaporation rate affect the architectural resolution, introducing a design process driven by matter. Digital Soil shows the potential of a fully reversible biodegradable manufacturing process for load-bearing architectural elements, opening up new fields of application for sustainable material systems that can enhance the ecological potential of architectural construction.